Factors influencing the rate of returns on initial public offerings a study on : KLSE’s second board / Rashdan Saferan Saat - Saat, Rashdan Saferan (1994)
The purpose of this project paper is to identify the forces that influence the rate of initial return on IPOs KLSE's Second Board. To ascertain these forces, six elements have been selected and have been tested as factors that may have influenced the rate of initial return on IPOs. The selected six elements were offer price, offering size, amount listed, the company age, PE ratio and the market level. This project paper was based on the findings from 84 IPOs. All those IPOs were listed on the KLSE's Second Board as at 31st. December 1993. The result shows that, on average, IPOs gave an initial return of 59.46% on the first day of listing. The rate of initial return was found to be influenced by the offer price and also market level (in this case, KLSE's Composite Index). The size of the offering, age of the company, PE ratio and the amount listed were found to have no significant relationship with the rate of initial return.